Download presentation
Presentation is loading. Please wait.
1
© T Madas
2
Expand and simplify these double brackets:
( x + 2 ) ( x + 3 ) = x 2 + 3x + 2x + 6 = x 2 + 5x + 6 ( x + 2 ) ( x – 4 ) = x 2 – 4x + 2x – 8 = x 2 – 2x – 8 ( x – 4 ) ( x – 1 ) = x 2 – x – 4x + 4 = x 2 – 5x + 4 ( x – 5 ) ( x – 4 ) = x 2 – 4x – 5x + 20 = x 2 – 9x + 20 ( x + 2 ) ( x – 2 ) = x 2 – 2x + 2x – 4 = x 2 – 4 ( x + 5 ) ( x + 2 ) = x 2 + 2x + 5x + 10 = x 2 + 7x + 10 ( x – 6 ) ( x + 3 ) = x 2 + 3x – 6x – 18 = x 2 – 3x – 18 ( x – 5 ) ( x – 7 ) = x 2 – 7x – 5x + 35 = x 2 – 12x + 35 © T Madas
3
Expand and simplify these double brackets:
( x + 2 ) ( x + 4 ) = x 2 + 4x + 2x + 8 = x 2 + 6x + 8 ( x + 7 ) ( x – 4 ) = x 2 – 4x + 7x – 28 = x 2 + 3x – 28 ( x – 7 ) ( x – 1 ) = x 2 – x – 7x + 7 = x 2 – 8x + 7 ( x – 9 ) ( x – 4 ) = x 2 – 4x – 9x + 36 = x 2 – 13x + 36 ( x + 3 ) ( x – 3 ) = x 2 – 3x + 3x – 9 = x 2 – 9 ( x + 5 ) ( x + 8 ) = x 2 + 8x + 5x + 10 = x 2 + 13x + 40 ( x – 6 ) ( x + 4 ) = x 2 + 4x – 6x – 24 = x 2 – 2x – 24 ( x – 3 ) ( x – 7 ) = x 2 – 7x – 3x + 21 = x 2 – 10x + 21 © T Madas
4
Expand and simplify these double brackets:
( 3x + 2 ) ( x + 3 ) = 3x 2 + 9x + 2x + 6 = 3x 2 + 11x + 6 ( 2x – 3 ) ( x – 1 ) = 2x 2 – 2x – 3x + 3 = 2x 2 – 5x + 3 ( x + 2 ) ( 5x – 4 ) = 5x 2 – 4x + 10x – 8 = 5x 2 + 6x – 8 ( x – 3 ) ( 2x – 5 ) = 2x 2 – 5x – 6x + 15 = 2x 2 – 11x + 15 ( 3x + 2 ) ( 3x – 2 ) = 9x 2 – 6x + 6x – 4 = 9x 2 – 4 ( 2x + 1 ) ( 3x + 2 ) = 6x 2 + 4x + 3x + 2 = 6x 2 + 7x + 2 ( 2x – 1 ) ( 4x + 3 ) = 8x 2 + 6x – 4x – 3 = 8x 2 + 2x – 3 ( 3x – 2 ) ( 5x – 7 ) = 15x 2 – 21x – 10x + 14 = 15x 2 – 31x + 14 © T Madas
5
© T Madas
6
Expand and simplify these double brackets:
( x + 2 ) ( x + 3 ) = x 2 + 3x + 2x + 6 = x 2 + 5x + 6 ( x + 2 ) ( x – 4 ) = x 2 – 4x + 2x – 8 = x 2 – 2x – 8 ( x – 4 ) ( x – 1 ) = x 2 – x – 4x + 4 = x 2 – 5x + 4 ( x – 5 ) ( x – 4 ) = x 2 – 4x – 5x + 20 = x 2 – 9x + 20 ( x + 2 ) ( x – 2 ) = x 2 – 2x + 2x – 4 = x 2 – 4 ( x + 5 ) ( x + 2 ) = x 2 + 2x + 5x + 10 = x 2 + 7x + 10 ( x – 6 ) ( x + 3 ) = x 2 + 3x – 6x – 18 = x 2 – 3x – 18 ( x – 5 ) ( x – 7 ) = x 2 – 7x – 5x + 35 = x 2 – 12x + 35 © T Madas
7
Expand and simplify these double brackets:
( x + 2 ) ( x + 4 ) = x 2 + 4x + 2x + 8 = x 2 + 6x + 8 ( x + 7 ) ( x – 4 ) = x 2 – 4x + 7x – 28 = x 2 + 3x – 28 ( x – 7 ) ( x – 1 ) = x 2 – x – 7x + 7 = x 2 – 8x + 7 ( x – 9 ) ( x – 4 ) = x 2 – 4x – 9x + 36 = x 2 – 13x + 36 ( x + 3 ) ( x – 3 ) = x 2 – 3x + 3x – 9 = x 2 – 9 ( x + 5 ) ( x + 8 ) = x 2 + 8x + 5x + 10 = x 2 + 13x + 40 ( x – 6 ) ( x + 4 ) = x 2 + 4x – 6x – 24 = x 2 – 2x – 24 ( x – 3 ) ( x – 7 ) = x 2 – 7x – 3x + 21 = x 2 – 10x + 21 © T Madas
8
Expand and simplify these double brackets:
( 3x + 2 ) ( x + 3 ) = 3x 2 + 9x + 2x + 6 = 3x 2 + 11x + 6 ( 2x – 3 ) ( x – 1 ) = 2x 2 – 2x – 3x + 3 = 2x 2 – 5x + 3 ( x + 2 ) ( 5x – 4 ) = 5x 2 – 4x + 10x – 8 = 5x 2 + 6x – 8 ( x – 3 ) ( 2x – 5 ) = 2x 2 – 5x – 6x + 15 = 2x 2 – 11x + 15 ( 3x + 2 ) ( 3x – 2 ) = 9x 2 – 6x + 6x – 4 = 9x 2 – 4 ( 2x + 1 ) ( 3x + 2 ) = 6x 2 + 4x + 3x + 2 = 6x 2 + 7x + 2 ( 2x – 1 ) ( 4x + 3 ) = 8x 2 + 6x – 4x – 3 = 8x 2 + 2x – 3 ( 3x – 2 ) ( 5x – 7 ) = 15x 2 – 21x – 10x + 14 = 15x 2 – 31x + 14 © T Madas
9
© T Madas
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.